Handbook of public economics - Arrow, Kenneth J (Ed.); Intriligator, Michael D (Ed.) (Amsterdam Elsevier, 1985)
The handbook of public economics is in two volumes.The firstvol.contents are-history of fiscal doctrine,public sector pricing,taxes and labour supply and tax policy in open economicsand the vol.two contents are-theory of public goods,incentives and alloca
Keywords: FINANCE, PUBLIC; FINANCE-GOVERNMENT POLICY; FISCAL POLICY